Features of designing induction magnetometers - V.O. Pronenko; V.E. Korepanov (Геофизический журнал, 2011)
Induction or search-coil magnetometers (IM) are widely used in many branches of science and industry, including field geophysics. The frequency range and dynamic range of IM are probably the widest of all existing magnetometers: they are used for the measurement of magnetic field variations in the frequency band from ~10-4 till ~106 Hz with the intensities from fractions of femtotesla till tens of tesla. This explains the permanent interest to IM design and the attempts to construct the IMs with the best possible parameters. The IM with optimal parameters set design peculiarities are described.